Synthetic Utility of Sugar-Derived Cyclic Nitrones: A Diastereoselective Synthesis of Linear 4-Azatriquinanes - Bandaru, Anandaraju; Kaliappan, Krishna P. (Synlett, 2012)
A diastereoselective Pauson–Khand reaction has been utilized as the key step in the construction of azatriquinanes from sugar-derived nitrones.
Keywords: diastereoselectivity; sugar derivatives; nitrones; Pauson–Khand reaction